2009
DOI: 10.1007/s10909-009-9885-z
|View full text |Cite
|
Sign up to set email alerts
|

To Wet or Not to Wet: That Is the Question

Abstract: Wetting transitions have been predicted and observed to occur for various combinations of fluids and surfaces. This paper describes the origin of such transitions, for liquid films on solid surfaces, in terms of the gas-surface interaction potentials V(r), which depend on the specific adsorption system. The transitions of light inert gases and H 2 molecules on alkali metal surfaces have been explored extensively and are relatively well understood in terms of the least attractive adsorption interactions in natu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 118 publications
(210 reference statements)
1
40
0
Order By: Relevance
“…The binding of inert gases to graphite is relatively strong; for helium it exceeds the binding between the gas atoms [1]. In addition to coverage and temperature, the corrugation of the surface, its curvature, and dimensionality control the physical properties of the adsorbate.…”
mentioning
confidence: 99%
“…The binding of inert gases to graphite is relatively strong; for helium it exceeds the binding between the gas atoms [1]. In addition to coverage and temperature, the corrugation of the surface, its curvature, and dimensionality control the physical properties of the adsorbate.…”
mentioning
confidence: 99%
“…2. We found that for 4 He on Cs, T w ≈ 2.0 ± 0.1 K and T pwc ≈ 2.5 K. We also found that at coexistence, the wetting transition was extremely hysteretic. If a dry state was prepared on the coexistence curve below T w , it would spontaneously wet at T = T w as the temperature was raised.…”
Section: Wetting Transitionsmentioning
confidence: 50%
“…3 He wets Cs at all temperatures, but the formation of a thick film proceeds via an approximately first order prewetting-like transition [20]. The liquid-vapor surface tension of 3 He is less than for 4 He, so the film state corresponding to Fig. 1B is stable even at T = 0.…”
Section: Wetting Transitionsmentioning
confidence: 92%
See 2 more Smart Citations